Question
upstudy study bank question image url

10. \( x^{\frac{1}{2}}-3 x^{\frac{1}{4}}+2= \) 43. \( x-x^{\frac{1}{2}}-20=0 \) 16. \( x-3 x^{\frac{1}{2}}-18= \) 19. \( x^{\frac{2}{3}}-3 x^{\frac{1}{3}}-4=0 \)

Ask by Bob Peters. in South Africa
Feb 02,2025

Real Tutor Solution

Tutor-Verified Answer

Answer

Solutions to the equations are: 1. \( x = 1 \) and \( x = 16 \) 2. \( x = 25 \) 3. \( x = 36 \) 4. \( x = 64 \) and \( x = -1 \)

Solution

Sure, let's solve each of the given equations step by step. --- ### **10.** \( \sqrt{x} - 3 \sqrt[4]{x} + 2 = 0 \) **Solution:** 1. **Substitute Variable:** Let \( y = \sqrt[4]{x} \). Then, \( \sqrt{x} = y^2 \). 2. **Rewrite the Equation:** \[ y^2 - 3y + 2 = 0 \] 3. **Factor the Quadratic:** \[ (y - 1)(y - 2) = 0 \] So, \( y = 1 \) or \( y = 2 \). 4. **Find \( x \):** \[ x = y^4 \] - If \( y = 1 \), then \( x = 1 \). - If \( y = 2 \), then \( x = 16 \). **Solutions:** \( x = 1 \) and \( x = 16 \) --- ### **43.** \( x - \sqrt{x} - 20 = 0 \) **Solution:** 1. **Substitute Variable:** Let \( y = \sqrt{x} \). Then, \( x = y^2 \). 2. **Rewrite the Equation:** \[ y^2 - y - 20 = 0 \] 3. **Solve the Quadratic:** \[ y = \frac{1 \pm \sqrt{1 + 80}}{2} = \frac{1 \pm 9}{2} \] - \( y = 5 \) or \( y = -4 \) 4. **Discard Negative Root:** Since \( y = \sqrt{x} \geq 0 \), \( y = 5 \). 5. **Find \( x \):** \[ x = 5^2 = 25 \] **Solution:** \( x = 25 \) --- ### **16.** \( x - 3\sqrt{x} - 18 = 0 \) **Solution:** 1. **Substitute Variable:** Let \( y = \sqrt{x} \). Then, \( x = y^2 \). 2. **Rewrite the Equation:** \[ y^2 - 3y - 18 = 0 \] 3. **Solve the Quadratic:** \[ y = \frac{3 \pm \sqrt{9 + 72}}{2} = \frac{3 \pm 9}{2} \] - \( y = 6 \) or \( y = -3 \) 4. **Discard Negative Root:** Since \( y = \sqrt{x} \geq 0 \), \( y = 6 \). 5. **Find \( x \):** \[ x = 6^2 = 36 \] **Solution:** \( x = 36 \) --- ### **19.** \( x^{\frac{2}{3}} - 3x^{\frac{1}{3}} - 4 = 0 \) **Solution:** 1. **Substitute Variable:** Let \( y = x^{\frac{1}{3}} \). Then, \( x^{\frac{2}{3}} = y^2 \). 2. **Rewrite the Equation:** \[ y^2 - 3y - 4 = 0 \] 3. **Solve the Quadratic:** \[ y = \frac{3 \pm \sqrt{9 + 16}}{2} = \frac{3 \pm 5}{2} \] - \( y = 4 \) or \( y = -1 \) 4. **Find \( x \):** \[ x = y^3 \] - If \( y = 4 \), then \( x = 64 \). - If \( y = -1 \), then \( x = -1 \). **Solutions:** \( x = 64 \) and \( x = -1 \) --- ### **Summary of Solutions:** 1. **Problem 10:** \( x = 1 \) and \( x = 16 \) 2. **Problem 43:** \( x = 25 \) 3. **Problem 16:** \( x = 36 \) 4. **Problem 19:** \( x = 64 \) and \( x = -1 \) --- If you have any further questions or need additional explanations, feel free to ask!

Reviewed and approved by the UpStudy tutoring team

error msg
Explain
Simplify this solution

The Deep Dive

For the expression \( x^{\frac{1}{2}} - 3 x^{\frac{1}{4}} + 2 \), you can simplify it by performing a substitution. Letting \( y = x^{\frac{1}{4}} \), the expression transforms to \( y^2 - 3y + 2 \), which can be factored into \( (y - 1)(y - 2) \). This leads to the solutions \( y = 1 \) or \( y = 2 \), and plugging back gives \( x = 1^4 = 1 \) or \( x = 2^4 = 16 \). Now, for \( x - x^{\frac{1}{2}} - 20 = 0 \), rearrange it as \( x - 20 = x^{\frac{1}{2}} \). Squaring both sides yields a quadratic equation \( x^2 - 40x + 400 = 0 \). Factoring gives \( (x - 20)^2 = 0 \), leading to \( x = 20 \) as a double solution, indicating it touches the x-axis at this point.

Try Premium now!
Try Premium and ask Thoth AI unlimited math questions now!
Maybe later Go Premium
Study can be a real struggle
Why not UpStudy it?
Select your plan below
Premium

You can enjoy

Start now
  • Step-by-step explanations
  • 24/7 expert live tutors
  • Unlimited number of questions
  • No interruptions
  • Full access to Answer and Solution
  • Full Access to PDF Chat, UpStudy Chat, Browsing Chat
Basic

Totally free but limited

  • Limited Solution
Welcome to UpStudy!
Please sign in to continue the Thoth AI Chat journey
Continue with Email
Or continue with
By clicking “Sign in”, you agree to our Terms of Use & Privacy Policy